(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
In the rapidly evolving field of civil engineering, proficiency in Computer-Aided Design (CAD) tools like AutoCAD is pivotal for modern design and construction practices. This study assesses the AutoCAD proficiency levels of civil engineering students in Cross River State, Nigeria, exploring its implications for advancing contemporary civil engineering practices. Using a descriptive survey design, data were collected from 384 students across three tertiary institutions through structured questionnaires and practical AutoCAD skill tests. Findings revealed that 62% of students demonstrated moderate proficiency, with significant gaps in advanced features like 3D modeling and parametric design. Demographic analysis indicated no significant gender-based differences, but proficiency varied by academic level, with final-year students outperforming others. Challenges included limited access to updated software, inadequate training facilities, and outdated curricula. These findings underscore the need for curriculum reform, enhanced training infrastructure, and industry-academia collaboration to align student skills with global standards. Recommendations include integrating advanced AutoCAD modules, establishing CAD laboratories, and fostering partnerships with engineering firms to enhance practical exposure. This study highlights the critical role of AutoCAD proficiency in preparing students for innovative civil engineering practices, contributing to sustainable infrastructure development in Nigeria.